2003
DOI: 10.1152/ajpcell.00374.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate receptors modulate Ca2+ sparks and Ca2+ store content in vas deferens myocytes

Abstract: White, Carl, and J. Graham McGeown. Inositol 1,4,5-trisphosphate receptors modulate Ca 2ϩ sparks and Ca 2ϩ store content in vas deferens myocytes. Am J Physiol Cell Physiol 285: C195-C204, 2003. First published March 5, 2003 10.1152/ajpcell.00374.2002 sparks were observed in fluo 4-loaded myocytes from guinea pig vas deferens with line-scan confocal imaging. They were abolished by ryanodine (100 M), but the inositol 1,4,5-trisphosphate (IP 3) receptor (IP3R) blockers 2-aminoethoxydiphenyl borate (2-APB; 100 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…In addition to muscle and alveolar type II cells, TRIC channel subtypes are likely to contribute to physiological Ca 2+ release in various additional cell types. The 'idling' levels of IP 3 generation and IP 3 receptor gating presumably constitute a Ca 2+ leakage machinery to modulate Ca 2+ stores and to elevate cytoplasmic Ca 2+ levels under basal conditions in several cell types (Mozhayeva and Mozhayeva, 1996;Lomax et al, 2002;White and McGeown, 2003). In this study, we detected reduced resting Ca 2+ levels in TRIC-B-knockout type II cells (Fig.…”
Section: Research Articlesupporting
confidence: 50%
“…In addition to muscle and alveolar type II cells, TRIC channel subtypes are likely to contribute to physiological Ca 2+ release in various additional cell types. The 'idling' levels of IP 3 generation and IP 3 receptor gating presumably constitute a Ca 2+ leakage machinery to modulate Ca 2+ stores and to elevate cytoplasmic Ca 2+ levels under basal conditions in several cell types (Mozhayeva and Mozhayeva, 1996;Lomax et al, 2002;White and McGeown, 2003). In this study, we detected reduced resting Ca 2+ levels in TRIC-B-knockout type II cells (Fig.…”
Section: Research Articlesupporting
confidence: 50%
“…The vas deferens of higher eukaryotes convey sperm from the testis to the exterior and are composed of smooth muscle. The smooth muscle of the rat vas deferens has a complex endomembrane system that contains high levels of IP 3 Rs (Villa et al, 1993), which appear to function both in the modulation of Ca 2ϩ sparks, and as a leak pathway to limit the Ca 2ϩ content of stores (White and McGeown, 2003). ITR-1 may play similar functions in regulating the contraction of the vas deferens through the activation of EGL-8, but it is also possible that they play a role in the upstream neuronal signals that trigger contraction.…”
Section: Egl-8 Regulates Sperm Transfer Through Activation Of Ip 3 Rsmentioning
confidence: 99%
“…36 IP 3 Rs are the intracellular Ca 2 þ release channels that have a key role in Ca 2 þ signaling in cells. 37 Growing evidence indicates that TNF-a upregulated IP 3 R1 expression, and that the upregulation correlates with alterations in Ca 2 þ homeostasis in many conditions. 38,39 We demonstrated in a recent study that TNF-a enhanced IP 3 R1 expression at mRNA and protein levels in HMCs, and identified TNFR1/ PC-PLC/PKCa-dependent and TNFR2-dependent IP 3 R1 genes.…”
Section: Discussionmentioning
confidence: 99%